Pengaruh Agens Hayati Terhadap Insiden Penyakit Bulai pada Jagung - Ratna Dwi Hirma Windriyati; Nur Kholida Wulansari; Rifqi Adisonda (Universitas Islam Raden Rahmat, Malang, 2024)
Downy mildew control with synthetic fungicides adversely affects it. The use of biological agents is an alternative because it is safer and environmentally friendly. The purpose of the study was to determine the effect of seed treatment using biological agents on corn seed viability, downy mildew and plant growth. Group Randomized Design (RAK) research method with three treatments and repeated 9 times. The treatment is K (without treatment), B (Bacillus subtilis and B. polymixa) and T (Trichoderma hamatum). B and T treatments were able to increase the viability of corn seeds as well as the length of roots and headers. Treatment B was more able to suppress the incidence and intensity of downy mildew compared to control and T. Treatment of the two biological agents was able to increase the number of leaves of corn plants and was not able to increase plant height, stem diameter and plant root weight.